2016
DOI: 10.1016/j.jfda.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and bioactivity of Formosan lauraceous plants

Abstract: Taiwan is rich in lauraceous plants. A review of 197 references based on the chemical analysis and bioactivity of indigenous lauraceous plants carried out by native scientists from 1963 to 2014 has been compiled. About 303 new compounds and thousands of known compounds comprising alkaloids and non-alkaloids with diverse structures have been isolated or identified from indigenous plants belonging to the 11 lauraceous genera. The volatile components, however, have been excluded from this review. This review prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 167 publications
1
12
0
Order By: Relevance
“…Terpinenes: 4-Terpineol; borneol; camphene; caryophyllene; cineol; Citral; citronellal; citronellol; geraniol; limonene; b-myrcene; b-pinene; ⍺pinene [154] Anticancer, [155] antiinflammatory, [154] antioxidant, [130] antiviral, [156] cytotoxicity [156] Headache, [157] blood circulation [157] Root Actinodaphnine [155,158]…”
Section: Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…Terpinenes: 4-Terpineol; borneol; camphene; caryophyllene; cineol; Citral; citronellal; citronellol; geraniol; limonene; b-myrcene; b-pinene; ⍺pinene [154] Anticancer, [155] antiinflammatory, [154] antioxidant, [130] antiviral, [156] cytotoxicity [156] Headache, [157] blood circulation [157] Root Actinodaphnine [155,158]…”
Section: Fruitmentioning
confidence: 99%
“…Cinnamic acid; cinnamyl alcohol; coumarin; kaempferitrin; kaempferol; p-hydroxybenzoic acid; stigmasterol; b-sitosterol [158] ; polysaccharides; dehydrosulfurenic acid; 15a-acetyldehydrosulfurenic acid [157]…”
Section: Stemmentioning
confidence: 99%
“…Compound 4 (1.0 mg, 3.5 µmol) and pyridine- d 5 (10.9 µL, 135.4 µmol) was transferred to a vial. The contents of the vial were dissolved in chloroform- d 1 (1090 µL, [ 4 ] = 3.5 mM). R -(−)-MPTA-Cl (10.9 µL, 58.3 µmol) was added to the vial, the vial was capped and the contents were stirred at room temperature (2–4 h).…”
Section: Methodsmentioning
confidence: 99%
“…They stand out, resulting in its economic benefits and diverse bioactivities. A previous investigation showed that some lauraceous plants exhibit bioactivities, such as cytotoxicity, anti-tuberculosis, anti-inflammatory, and antiplatelet activities [ 4 ]. Recently, we completed the anti-inflammatory screening of 174 methanolic extracts from 60 Taiwanese lauraceous plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation